Method for preparing copper-based graphene composite foil through deep eutectic solvent electrodeposition
By using eutectic solvents and graphene dispersion technology during the electrodeposition process, the problem of graphene agglomeration in water-based solutions is solved, and the good dispersion and performance improvement of copper-based graphene composite materials is achieved, meeting the high performance requirements of the industry.
Patent Information
- Application Number
- CN202411721783.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-28
AI Technical Summary
In water-based solutions, graphene is prone to agglomeration and difficult to remain dispersed for a long time during the electrodeposition process, resulting in unstable performance of the composite material.
A low eutectic solvent (a mixed solvent of choline chloride and ethylene glycol) is used as the basis for the electrodeposition solution, and it is completely dissolved by heating and mechanical stirring. On this basis, copper chloride and gelatin dihydrate are added, followed by graphene and ultrasonic and high-speed homogeneous dispersion to prepare a composite electrolyte of copper-based graphene composite material.
It achieves good dispersion of graphene, improves the surface flatness and tissue density of composite materials, meets the use requirements of the microelectronics and battery industries, and reduces costs and environmental pollution.
Smart Images

Figure CN119530901A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and specifically discloses a method for preparing a copper-based graphene composite foil by electrodeposition of a low eutectic solvent. Background Art
[0002] Copper has high electrical and thermal conductivity as well as good mechanical properties. Therefore, copper electrodeposition is widely used in electronic applications, batteries, printed circuit boards, aerospace and other fields. As far as electrodeposition technology is concerned, electrodeposition with water-based solutions is the most important application technology. The coating that meets the performance requirements can be prepared by changing the temperature, current density, plate spacing, type and concentration of additives, etc. However, water-based solutions also have some disadvantages, such as hydrogen precipitation during electrodeposition, relatively low solubility of certain copper salts in water, sensitivity to temperature changes and environmental pollution. Low eutectic solvents have the advantages of high current efficiency, high deposition rate, wider solubility, better temperature stability and environmental friendliness.
[0003] Graphene has extremely high strength and electrical and thermal conductivity, and is an ideal reinforcement phase. However, the preparation of composite electrolytes with graphene as the reinforcement phase usually faces a problem, that is, graphene is very easy to agglomerate in water-based solutions due to its own characteristics. Surfactants such as polyacrylic acid, sodium dodecyl sulfate, and polyvinyl pyrrolidone are usually added to promote the dispersion of graphene in water-based solutions. However, the effect of these surfactants is limited and it is difficult to support long-term electrodeposition production. Summary of the invention
[0004] In order to solve the technical problems pointed out in the background technology, the present invention provides a method for preparing copper-based graphene composite foil by electrodeposition of a low eutectic solvent.
[0005] The preparation method of the copper-based graphene-based composite foil comprises the following specific steps:
[0006] (1) Preparation of a low eutectic solvent: The preparation method is as follows: Due to the strong water absorption of choline chloride, choline chloride needs to be placed in a drying oven and then weighed. Then, choline chloride and ethylene glycol are weighed and mixed in a molar ratio of 1:1.5 to 1:2.5, and heated in an oil bath at 60 to 80°C and mechanically stirred until dissolved.
[0007] (2) preparing a cupric chloride solution: adding cupric chloride dihydrate and gelatin to the low eutectic solvent of step (1) at concentrations of 20 to 50 g / L and 10 to 50 mg / L, respectively, heating in an oil bath at 50° C. and mechanically stirring until dissolved, and then adding deionized water.
[0008] (3) Preparation of copper-based graphene electrodeposition solution: adding graphene to a cupric chloride solution at a concentration of 0.05 to 2.0 g / L, firstly performing ultrasonic dispersion, and then performing high-speed homogenization dispersion to obtain a composite electrolyte for preparing a copper-based graphene composite material.
[0009] (4) Use 1000 mesh, 1500 mesh and 2000 mesh sandpaper to polish the plates in turn, and then put the polished anode and cathode plates into 10% dilute hydrochloric acid solution for activation for 5 to 10 minutes.
[0010] (5) Using the composite electrolyte prepared in step (3) to carry out direct current electrodeposition, the electrodeposition process parameters are: current density of 5 to 60 mA / cm 2 The deposition liquid temperature is 20-50°C, the deposition time is 0.5-3h, magnetic stirring is performed during electrodeposition, and the rotation speed is 80-200r / min.
[0011] The composite electrodeposition liquid used in the present invention has a reasonable composition ratio and can be recycled, has a better graphene dispersion effect, and achieves cost savings and environmental protection; the composite foil prepared by using the electrodeposition liquid has a smooth surface, a uniform and dense structure, and its surface roughness, mechanical properties and thermal conductivity meet the use requirements of the microelectronics and battery industries.
[0012] Beneficial effects of the present invention
[0013] 1. The process of the present invention is simple, and the prepared composite material has fine surface particles, low surface roughness, and excellent mechanical properties and thermal conductivity.
[0014] 2. The present invention provides a new composite deposition liquid formula, which replaces the traditional water-based solvent with a low eutectic solvent. While fully dispersing graphene, it also has the advantages of high conductivity, wide electrochemical window and good thermal stability.
[0015] 3. The sedimentation liquid of the present invention is environmentally friendly, does not require the addition of excessive additives or sulfate acid, etc., and has low toxicity and biodegradability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a surface scanning electron microscope image of the composite foil prepared in Example 3.
[0017] Figure 2 This is a three-dimensional image of the surface morphology of the composite foil obtained in Example 3.
[0018] Figure 3 This is a three-dimensional image of the surface morphology of the composite foil prepared in Comparative Example 3.
[0019] Figure 4 This is a comparison diagram of the composite electrolyte prepared in Example 3 before and after standing for 24 hours.
[0020] Figure 5 This is a comparison chart of the composite electrolyte prepared in Comparative Example 3 before and after standing for 24 hours. DETAILED DESCRIPTION
[0021] The present invention is further described in detail below in conjunction with embodiments: The following embodiments are all based on the configuration of 250 mL of the electrodeposition solution of the copper-based graphene composite material as an example.
[0022] Example 1
[0023] The composition ratio of the copper-based graphene electrodeposition solution is: 35 g / L of cupric chloride dihydrate, 0.8 g / L of graphene, 30 ml of deionized water, and the balance is a choline chloride (ChCl)-ethylene glycol (EG) low eutectic solvent; the additive is: 20 mg / L of gelatin.
[0024] The preparation method of the ChCl-EG low eutectic solvent is as follows: put ChCl into a drying oven for drying and then weigh it, then weigh EG at a molar ratio of 1:2 to ChCl, heat it in an oil bath at 80°C and stir it mechanically until it is dissolved.
[0025] The preparation method of copper-based graphene electrodeposition liquid is as follows: add copper chloride dihydrate and gelatin into a low eutectic solvent, heat in a 50°C oil bath and mechanically stir until dissolved, and add deionized water after all dissolved; add graphene into the copper chloride solution, perform ultrasonic dispersion after mechanical stirring, and finally perform high-speed homogenization dispersion to obtain a composite electrodeposition liquid.
[0026] Pretreatment of the anode and cathode plates: Use metallographic sandpaper to polish the anode and cathode plates to remove surface stains and oxide films, and then place the plates in a 10% dilute hydrochloric acid solution for 5 minutes for activation.
[0027] The electrodeposition process parameters are: current density is 10mA / cm 2 The deposition liquid temperature was 30 °C, the deposition time was 2 h, magnetic stirring was performed during electrodeposition, and the rotation speed was 200 r / min.
[0028] The composite deposited layer prepared under this condition has a relatively uneven macroscopic surface with concave and convex fascia, a relatively large particle size on the microscopic surface morphology, and average density. The tensile strength of the deposited layer reaches 412±10MPa, the thermal conductivity can reach 475W / m·K, and the surface roughness reaches 1.27μm.
[0029] Example 2
[0030] The composition ratio of the copper-based graphene electrodeposition solution is: 35 g / L of cupric chloride dihydrate, 0.8 g / L of graphene, 15 ml of deionized water, and the balance is ChCl-EG low eutectic solvent; the additive is: 20 mg / L of gelatin.
[0031] The preparation method of ChCl-EG low eutectic solvent is the same as that in Example 1.
[0032] The configuration method of the copper-based graphene electrodeposition solution is the same as that of Example 1.
[0033] The pretreatment of the anode and cathode plates is the same as in Example 1.
[0034] The electrodeposition process parameters are the same as those in Example 1.
[0035] The composite deposited layer prepared under this condition has slight fascia on the macroscopic surface, small particles on the microscopic surface morphology, good density, the tensile strength of the deposited layer reaches 573±10MPa, the thermal conductivity can reach 628W / m·K, and the surface roughness reaches 0.83μm.
[0036] Example 3
[0037] The composition ratio of the copper-based graphene electrodeposition solution is: 35 g / L of cupric chloride dihydrate, 0.8 g / L of graphene, and the balance is a ChCl-EG low eutectic solvent; the additive is: 20 mg / L of gelatin.
[0038] The preparation method of ChCl-EG low eutectic solvent is the same as that in Example 1.
[0039] The preparation method of copper-based graphene electrodeposition liquid is as follows: adding cupric chloride dihydrate and gelatin into a ChCl-EG low eutectic solvent, heating in an oil bath at 50°C and mechanically stirring until dissolved; adding graphene into the cupric chloride solution, mechanically stirring and then ultrasonically dispersing, and finally high-speed homogenizing and dispersing to obtain a composite electrodeposition liquid.
[0040] The pretreatment of the anode and cathode plates is the same as in Example 1.
[0041] The electrodeposition process parameters are the same as those in Example 1.
[0042] The composite deposited layer prepared under this condition has a smooth macroscopic surface, extremely small microscopic surface particles, good density, the tensile strength of the deposited layer reaches 835±10MPa, the thermal conductivity can reach 797W / m·K, and the surface roughness reaches 0.28μm.
[0043] Example 4
[0044] The composition ratio of the copper-based graphene electrodeposition solution is the same as that of Example 3.
[0045] The preparation method of the ChCl-EG low eutectic solvent is as follows: put ChCl into a drying oven and dry it, then weigh it, and then weigh EG at a molar ratio of 1:1.5 to ChCl, heat it in an oil bath at 80°C and stir it mechanically until it is dissolved.
[0046] The configuration method of the copper-based graphene electrodeposition solution is the same as that of Example 3.
[0047] The pretreatment of the anode and cathode plates is the same as in Example 1.
[0048] The electrodeposition process parameters are the same as those in Example 1.
[0049] The composite deposited layer prepared under this condition has a smooth macroscopic surface, small microscopic surface particles, good density, tensile strength of the deposited layer reaches 553±10MPa, thermal conductivity can reach 642W / m·K, and surface roughness reaches 0.64μm.
[0050] Example 5
[0051] The composition ratio of the copper-based graphene electrodeposition solution is the same as that of Example 3.
[0052] The preparation method of the ChCl-EG low eutectic solvent is as follows: put ChCl into a drying oven for drying and then weigh it, then weigh EG at a molar ratio of 1:2.5 to ChCl, heat it in an oil bath at 80°C and stir it mechanically until it is dissolved.
[0053] The configuration method of the copper-based graphene electrodeposition solution is the same as that of Example 3.
[0054] The pretreatment of the anode and cathode plates is the same as in Example 1.
[0055] The electrodeposition process parameters are the same as those in Example 1.
[0056] The composite deposited layer prepared under this condition has a relatively smooth macroscopic surface, large particles, pores and poor density on the microscopic surface. The tensile strength of the deposited layer reaches 373±10MPa, the thermal conductivity can reach 489W / m·K, and the surface roughness reaches 1.47μm.
[0057] Example 6
[0058] The composition ratio of the copper-based graphene electrodeposition solution is: 35 g / L of cupric chloride dihydrate, 0.4 g / L of graphene, and the balance is a ChCl-EG low eutectic solvent; the additive is: 20 mg / L of gelatin.
[0059] The preparation method of ChCl-EG low eutectic solvent is the same as that in Example 1.
[0060] The configuration method of the copper-based graphene electrodeposition solution is the same as that of Example 3.
[0061] The pretreatment of the anode and cathode plates is the same as in Example 1.
[0062] The electrodeposition process parameters are the same as those in Example 1.
[0063] The composite deposited layer prepared under this condition has a smooth macroscopic surface, fine microscopic surface morphology, good density, tensile strength of the deposited layer reaches 681±10MPa, thermal conductivity can reach 764W / m·K, and surface roughness reaches 0.33μm.
[0064] Example 7
[0065] The composition ratio of the copper-based graphene electrodeposition solution is: 35 g / L of cupric chloride dihydrate, 1.2 g / L of graphene, and the balance is a ChCl-EG low eutectic solvent; the additive is: 20 mg / L of gelatin.
[0066] The preparation method of ChCl-EG low eutectic solvent is the same as that in Example 1.
[0067] The configuration method of the copper-based graphene electrodeposition solution is the same as that of Example 3.
[0068] The pretreatment of the anode and cathode plates is the same as in Example 1.
[0069] The electrodeposition process parameters are the same as those in Example 1.
[0070] The composite deposited layer prepared under this condition has a relatively rough macroscopic surface with protruding particles, and a microscopic surface with large particles, pores, and poor density. The tensile strength of the deposited layer reaches 337±10MPa, the thermal conductivity can reach 362W / m·K, and the surface roughness reaches 1.86μm.
[0071] Example 8
[0072] The composition ratio of the copper-based graphene electrodeposition solution is the same as that of Example 3.
[0073] The preparation method of ChCl-EG low eutectic solvent is the same as that in Example 1.
[0074] The configuration method of the copper-based graphene electrodeposition solution is the same as that of Example 3.
[0075] The pretreatment of the anode and cathode plates is the same as in Example 1.
[0076] The electrodeposition process parameters are: current density is 5 mA / cm 2 The deposition liquid temperature was 30 °C, the deposition time was 2 h, magnetic stirring was performed during electrodeposition, and the rotation speed was 200 r / min.
[0077] The composite deposited layer prepared under this condition has a smooth macroscopic surface, small microscopic surface particles and good density, but the deposition rate is low and the deposited layer is thin. The tensile strength of the deposited layer reaches 662±10MPa, the thermal conductivity can reach 741W / m·K, and the surface roughness reaches 0.31μm.
[0078] Example 9
[0079] The composition ratio of the copper-based graphene electrodeposition solution is the same as that of Example 3.
[0080] The preparation method of ChCl-EG low eutectic solvent is the same as that in Example 1.
[0081] The configuration method of the copper-based graphene electrodeposition solution is the same as that of Example 3.
[0082] The pretreatment of the anode and cathode plates is the same as in Example 1.
[0083] The electrodeposition process parameters are: current density is 15mA / cm 2 The deposition liquid temperature was 30 °C, the deposition time was 2 h, magnetic stirring was performed during electrodeposition, and the rotation speed was 200 r / min.
[0084] The composite deposited layer prepared under this condition has a relatively rough macroscopic surface with protruding particles, and a microscopic surface with large particles, no pores, and average density. The tensile strength of the deposited layer reaches 451±10MPa, the thermal conductivity can reach 537W / m·K, and the surface roughness reaches 1.39μm.
[0085] Comparative Example 1
[0086] The composition ratio of the copper-based graphene electrodeposition solution is: 35 g / L of cupric chloride dihydrate, 0.8 g / L of graphene, and the balance is a choline chloride (ChCl)-urea (Urea) low eutectic solvent; the additive is: 20 mg / L of gelatin.
[0087] The preparation method of ChCl-Urea low eutectic solvent is as follows: put ChCl into a drying oven to dry and then weigh it, then weigh Urea in a molar ratio of 1:2 to ChCl, heat it in an oil bath at 80°C and stir it mechanically until it dissolves.
[0088] The preparation method of copper-based graphene electrodeposition liquid is as follows: adding cupric chloride dihydrate and gelatin into a ChCl-Urea low eutectic solvent, heating in an oil bath at 50°C and mechanically stirring until dissolved; adding graphene into the cupric chloride solution, mechanically stirring and then ultrasonically dispersing, and finally high-speed homogenizing and dispersing to obtain a composite electrodeposition liquid.
[0089] The pretreatment of the anode and cathode plates is the same as in Example 1.
[0090] The electrodeposition process parameters are the same as those in Example 1.
[0091] The composite deposited layer prepared under this condition has a rough macroscopic surface, a large number of protruding particles, pores on the microscopic surface, and poor density. The tensile strength of the deposited layer reaches 187±10MPa, the thermal conductivity can reach 281W / m·K, and the surface roughness reaches 3.87μm.
[0092] Comparative Example 2
[0093] The composition ratio of the copper-based graphene electrodeposition solution is: 35 g / L of cupric chloride dihydrate, 0.8 g / L of graphene, and the balance is a choline chloride (ChCl)-glycerol (Gly) low eutectic solvent; the additive is: 20 mg / L of gelatin.
[0094] The preparation method of the ChCl-Gly low eutectic solvent is as follows: put ChCl into a drying oven and dry it, then weigh it, and then weigh Gly in a molar ratio of 1:1.5 with ChCl, heat it in an oil bath at 70°C and stir it mechanically until it is dissolved.
[0095] The preparation method of copper-based graphene electrodeposition liquid is as follows: adding cupric chloride dihydrate and gelatin into a ChCl-Gly low eutectic solvent, heating in an oil bath at 50°C and mechanically stirring until dissolved; adding graphene into the cupric chloride solution, mechanically stirring and then ultrasonically dispersing, and finally high-speed homogenizing and dispersing to obtain a composite electrodeposition liquid.
[0096] The pretreatment of the anode and cathode plates is the same as in Example 1.
[0097] The electrodeposition process parameters are the same as those in Example 1.
[0098] The composite deposition layer prepared under this condition is not formed but in powder form.
[0099] Comparative Example 3
[0100] The composition ratio of the graphene / copper water-based electrodeposition solution is: 180 g / L copper sulfate pentahydrate, 0.8 g / L graphene, and the balance is deionized water; the additive concentration is: 20 mg / L gelatin, 0.6 g / L SDS.
[0101] The pretreatment of the anode and cathode plates is the same as in Example 1.
[0102] The preparation method of the graphene / copper water-based electrodeposition liquid is as follows: ultrasonically dispersing SDS and a graphene solution, and then performing high-speed homogenization dispersion; adding gelatin to a copper sulfate solution, and mechanically stirring and dissolving; mechanically stirring and mixing the graphene solution and the copper sulfate solution, adjusting the pH value to 1 with sulfuric acid, and then performing ultrasonic dispersion to obtain a graphene / copper water-based electrodeposition liquid.
[0103] The electrodeposition process parameters are: temperature 20°C; current density 70 mA / cm 2 ; Electrodeposition time is 1h; Mechanical stirring is performed during deposition, and the stirring speed is 150r / min. Under this condition, the composite deposition layer prepared has a relatively uniform thickness, a flat surface, good density, a tensile strength of the deposition layer of 421±10MPa, a thermal conductivity of 453W / m·K, and a surface roughness of 1.75μm.
[0104] The above-described embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-described implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.
Claims
1. A method for preparing a copper-based graphene composite foil by electrodeposition of a low eutectic solvent, characterized in that: The method steps are as follows: (1) preparing a choline chloride and ethylene glycol deep eutectic solvent; (2) adding cupric chloride dihydrate and gelatin to the low eutectic solvent prepared in step (1), heating in an oil bath and mechanically stirring until dissolved to obtain a cupric chloride solution; (3) fully dispersing the graphene in the copper chloride solution obtained in step (2), and mixing by magnetic stirring to obtain an electrodeposition solution of a copper-based graphene composite material; (4) Use metallographic sandpaper to polish the anode copper plate and cathode titanium plate to remove oil stains and oxide film, and then use 10% dilute hydrochloric acid solution to activate the plates for 5 to 10 minutes; (5) Using the electrodeposition solution prepared in step (3) to perform direct current electrodeposition to obtain a copper-based graphene composite foil.
2. The method for preparing a copper-based graphene composite foil by electrodeposition of a low eutectic solvent according to claim 1, characterized in that: In step (1), the preparation method of the low eutectic solvent is: choline chloride and ethylene glycol are mixed in a molar ratio of 1:1.5 to 1:2.5, heated in an oil bath at 60 to 80° C. and mechanically stirred until dissolved, to obtain a low eutectic solvent.
3. The method for preparing a copper-based graphene composite foil by electrodeposition of a low eutectic solvent according to claim 1, characterized in that: The copper-based graphene composite material electrodeposition solution prepared in step (3) is composed of: 20-50 g / L of cupric chloride dihydrate, 10-50 mg / L of gelatin, 0.05-2.0 g / L of graphene, 0-120 mg / L of deionized water, and the balance is a low eutectic solvent.
4. The method for preparing a copper-based graphene composite foil by electrodeposition of a low eutectic solvent according to claim 1, characterized in that: In step (5), the electrodeposition parameters are: current density 5-60 mA / cm 2 The electrodeposition time is 0.5 to 3 hours; the temperature of the deposition solution is 20 to 50°C, magnetic stirring is performed during electrodeposition, and the rotation speed is 80 to 200 r / min.
5. The method for preparing copper-based graphene composite foil by electrodeposition of a low eutectic solvent according to claim 1, characterized in that: In step (5), the tensile strength of the prepared copper-based graphene composite foil is 337-835 MPa, the thermal conductivity is 362-797 W / m·K, and the surface roughness is 0.28-1.86 μm.
6. The method for preparing copper-based graphene composite foil by electrodeposition of a low eutectic solvent according to claim 1, characterized in that: In step (5), the prepared copper-based graphene composite foil is used as a heat conduction material.
Citation Information
Patent Citations
Preparation method for graphene
CN106829941A
Preparation method of copper based graphene composite with high heat conductivity
CN110408969A
High-strength high-thermal-conductivity low-roughness graphene / copper composite material and preparation method thereof
CN115418200A